2014
DOI: 10.1371/journal.pone.0110698
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and Expression Profiling of MicroRNAs in the Brain, Liver and Gonads of Marine Medaka (Oryzias melastigma) and in Response to Hypoxia

Abstract: The marine medaka (Oryzias melastigma) has been increasingly used as a fish model for detecting environmental stresses and chemical contaminants in the marine environment. Recent mammalian studies have shown that environmental stresses can alter the expression profiles of microRNAs (miRNAs), leading to transgenerational effects. Here, we use high-throughput Illumina RNA sequencing (RNA-Seq) for miRNA transcriptome analysis of brain, liver, and gonads from sexually mature male and female marine medaka. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…In this study, about 50% of genes annotated in the sheep genome were covered by more than 80% of the sequenced reads, demonstrating that RNA-Seq was more sensitive in finding transcripts, even for genes with low expression patterns, which is in agreement with Wang et al (2009). Although several recent studies have identified DEGs in the liver tissue of pigs (Gunawan et al, 2013a,b;Sodhi et al, 2014), cows (Graugnard et al, 2013), rats (Tran and Huang, 2014;Wang et al, 2014) and fish (Yang et al, 2012;Lau et al, 2014;Magnanou et al, 2014) when using next-generation sequencing platforms, very few studies have clarified transcriptomic analyses regarding the liver tissue of sheep. In this study, seven genes were found to be differentially expressed (three were upregulated and four downregulated) in a DEG analysis comparing the liver tissues of the LCL and MCL libraries.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In this study, about 50% of genes annotated in the sheep genome were covered by more than 80% of the sequenced reads, demonstrating that RNA-Seq was more sensitive in finding transcripts, even for genes with low expression patterns, which is in agreement with Wang et al (2009). Although several recent studies have identified DEGs in the liver tissue of pigs (Gunawan et al, 2013a,b;Sodhi et al, 2014), cows (Graugnard et al, 2013), rats (Tran and Huang, 2014;Wang et al, 2014) and fish (Yang et al, 2012;Lau et al, 2014;Magnanou et al, 2014) when using next-generation sequencing platforms, very few studies have clarified transcriptomic analyses regarding the liver tissue of sheep. In this study, seven genes were found to be differentially expressed (three were upregulated and four downregulated) in a DEG analysis comparing the liver tissues of the LCL and MCL libraries.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, data from RNA-Seq can help identify new transcripts (Hansey et al, 2012), single nucleotide polymorphisms (Esteve-Codina et al, 2011), alternative splicing events (Xiong et al, 2012), and other information. Several recent studies have used this type of next-generation sequencing platform in the liver tissue of pigs (Gunawan et al, 2013a,b;Sodhi et al, 2014), cows (Graugnard et al, 2013), rats (Tran and Huang, 2014;Wang et al, 2014), and fish (Yang et al, 2012;Lau et al, 2014;Magnanou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…But studies of the functional role of miRNA in teleosts are still limited. By using a small RNA sequencing platform, we have reported the profile of miRNA in different tissues of marine medaka, O. melastigma (Lau et al, 2014). Our previous studies also demonstrated that the global environmental problem of hypoxia is that it acts as an endocrine disruptor, resulting in reproductive impairment of aquatic fish (Shang et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…We have shown the induction of miR-210 in ovarian follicular cells under hypoxic stress. Furthermore, we used bioinformatics algorithms together with our recent de novo transcriptome reports of O. melastigma to strengthen the target gene prediction of miR-210 in the ovary of marine medaka (Lai et al, 2015;Lau et al, 2014). The top 10 ranked biological processes in gene ontology (GO) analysis suggested the roles of miR-210 in cell apoptosis, cell division, cell cycle, and cell differentiation of ovarian cells in response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…A next-generation sequencing-based approach revealed miR-9 modulation in a marine model of hypometabolism, the aestivating sea cucumber A. japonicus [7]. Interestingly, the marine medaka Oryzias melastigma, a fish model used to characterize responses to environmental stresses, displayed reduced miR-9 levels under hypoxia [28]. Recent work also reported miR-9 induction in hypoxic rat pulmonary artery smooth muscle cells further highlighting the potential importance of this miRNA in the hypoxic response [42].…”
Section: Discussionmentioning
confidence: 98%